2016
DOI: 10.3892/ol.2016.5351
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant promoter methylation of cancer-related genes in human breast cancer

Abstract: The clinical relevance of aberrant DNA methylation is being increasingly recognized in breast cancer. The present study aimed to evaluate the promoter methylation status of seven candidate genes and to explore their potential use as a biomarker for the diagnosis of breast cancer. A total of 70 Chinese patients with breast cancer were recruited, and matched with 20 patients with benign breast disease (BBD). Methylation-specific polymerase chain reaction was performed to measure the methylation status of selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
24
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 49 publications
7
24
0
4
Order By: Relevance
“…GSTP1 is involved in the detoxification functions, however its silencing appears closely related to the neoplastic transformation. This evidence suggests a possible role for GSTP1 as a prognostic marker [177].…”
Section: Detoxification Proteinsmentioning
confidence: 96%
“…GSTP1 is involved in the detoxification functions, however its silencing appears closely related to the neoplastic transformation. This evidence suggests a possible role for GSTP1 as a prognostic marker [177].…”
Section: Detoxification Proteinsmentioning
confidence: 96%
“…Thanaa Fathy Moghazy 1 , Hoda Aly Elattar 1 , Mona Kamal Eldeeb 1 *, Radwa Mohammed Rashad 1 , Ayman Mohamed Farouk 2 , Assmaa Mostafa Farrag 1 cytotoxic, carcinogenic agents (Wu et al, 2016) and conjugation of hormones as estrogen (Schnekenburger at al., 2014).…”
Section: Methylation Of Glutathione-s-transferase P1 Promotor In Egypmentioning
confidence: 99%
“…Previous epidemiological studies have reported that obesity (2), utilization of estrogen and progestin (3), advanced maternal age at first birth (4) and alcohol abuse (5) increase the risk of developing BC. In addition, genetic mutations and epigenetic modifications are regarded as potential causes of tumorigenesis in BC (6,7). In the past decades, there has been considerable progress in preventing, diagnosing and treating BC.…”
Section: Introductionmentioning
confidence: 99%